Poziom rozwoju życia religijnego młodzieży z ośrodka wychowawczego - Dariusz Buksik (Nicolaus Copernicus University in Toruń, 2009)
Religious development is a long-lasting and gradual process. Being, at the same   time, determined by a variety of factors originating from both conditions of outer nature   such as upbringing and certain inner circumstances like personal experience it is   also a very burdensome one. An important moment in the development of religiousness   is when a man becomes mature and independent due to establishing one's own views.   Many authorities point that a well-developed religiousness should be reflected on in the   process of upbringing, prevention and rehabilitation of certain kind. Previous experience   of religiousness might begin the process of changing the awareness of people undergoing   rehabilitation. The main aim of this work is to show and analyse the level of religiousness   of a young man undergoing the process of upbringing and rehabilitation at a juvenile   detention centre. On such a basis conclusions of educational nature which should foster   the development of mature personality with reference to certain spheres of religiousness   shall also be drawn in this work.